Enlarging the knowledge transfer realm through engagement with research stakeholders: a conversation attempt with action research - Joaquín M. Azagra-Caro; Alejandra Boni (Tapuya, 2023)
ABSTRACTMany knowledge transfer studies analyze channels that carry knowledge from university to industry and society. Action research has become a method to produce and transfer scientific knowledge at the same time; however, knowledge transfer studies rarely employ action research, and action research has rarely addressed the topic of knowledge transfer. Hence, there have been few opportunities to reflect upon the boundaries between the object of knowledge transfer studies and the knowledge transfer embodied in action research. Here, we present a first theoretical attempt to fill this gap, clarifying the concepts at play and drawing lessons for knowledge transfer studies about the dimensions through which knowledge transfer occurs in the communicative space generated during action research. We also ground our reflections on the suitability of introducing action research in knowledge transfer studies by conducting interviews with some of the most influential researchers in the field. Action research is posited as a way to increase engagement with research stakeholders, as called for by current demands to achieve higher societal impact. Engagement is highlighted as a source of key concepts and improved interpretation of results in knowledge transfer studies.